Exploring primary school teachers’ competencies of alternative assessment and evaluation [Sınıf öğretmenlerinin alternatif ölçme ve değerlendirme yeterliklerinin belirlenmesi] - ÇAKIR, MUSTAFA (Ankara University, 2015)
Primary school teachers’ competencies and self-efficacy beliefs of alternative assessment techniques were investigated and conditions in which they utilize such techniques in the classroom were explored within the framework of performance indicators set by the Ministry of National Education (MEB). Nine participants from three different schools in İstanbul participated in this qualitative case study. Purposeful sampling method was used in determining the participants. Data was collected through semi-structured interviews with participants and through classroom observations. Findings suggested that primary school teachers employed performance evaluation, portfolio, project and self-assessment techniques in their teaching practices. Among performance indicators providing feedback was significantly obvious than others. Twenty four (24) performance indicators of competence, identified and described by Ministry of Education, and analysis of classroom obsevations showed that participants’ avarege score of performance competence was 13.4. In conclusion, primary school teachers need support not only in understanding of alternative assessment and evaluation, but also in how to incorporate these practices into their teaching. © 2015, Ankara University. All rights reserved.
Keywords: Alternative assessment and evaluation; Primary school teachers; Teachers adequacy